FIZIKALÍQ ZORÍǴIWDÍŃ TÚRLI REJIMLERINDE JAS SPORTShÍLARDA JÚREK-QAN TAMÍR SISTEMASÍNÍŃ ADAPTACIYALÍQ ÓZGERIWShEŃLIGI - Bekmurzaev, A.Q. (SCIENCE and SOCIETY, 2026)
The article examines the peculiarities of cardiovascular adaptation in young athletes aged 14-15 when performing physical exercises of varying intensity. Analysis of heart rate and heart rate variability indicators at rest and after exertion are presented functional examination data. It has been shown that regular training activities form the economy of cardiac activity and increase the body's adaptive capabilities. The obtained results can be used in optimizing the training process and preventing functional overstrain in young-athletes.